Toward sustainable development: A methodology for evaluating environmental planning systems. (11th July 2018) - Zeiger, Bastion; Gunton, Thomas; Rutherford, Murray
Abstract: At the 1992 United Nations Conference on Environment and Development in Rio de Janeiro, the world's national governments committed to preparing strategies to achieve sustainable development. This paper describes an evaluation framework for measuring the success of these efforts to achieve environmental goals in sustainable development. The framework evaluates two dimensions of sustainable development planning: the environmental planning system, and environmental outcomes. An application of the methodology to evaluate environmental performance in Germany illustrates that the proposed method is relatively easy to apply, transparent, and identifies the strengths and weaknesses of a country's environmental performance.